Advisors perceptions of their role in supporting farm succession and inheritance. Issue 5 (19th October 2020) - Russell, Tomás; Breen, James; Gorman, Monica; Heanue, Kevin
ABSTRACT: Purpose: This paper examines the role of agricultural advisors in supporting farm families on the complex processes associated with farm succession and inheritance. Design/Methodology/approach: An online survey was conducted of all 256 public sector agricultural advisors in Ireland, examining their role, knowledge, training and support requirements in providing advice on succession and inheritance to farm families. Findings: Agricultural advisors have a key role to play in providing advice to farmers on the succession stage of farm transfer, particularly at the initial stages of the process where a high level of trust is required, and the provision of information is key. In terms of supporting farmers in this process the advisors do not feel they have the knowledge and skills required. Agricultural advisors need a model of training which reflects the subject of succession and inheritance in a softer more reflective approach. Theoretical Implications: This study highlights a new dimension to the extension literature, by identifying very specific roles for agricultural advisors in supporting farm families on farm succession and inheritance decisions and the attendant training and resource requirements. Practical implications: Teagasc agricultural advisors have a key role to play in providing advice on succession and inheritance, and due to their independent position and trust-based relationship with farmers, they require more knowledge, training and resources to effectively provide such advice. Originality/Value: The paper captures a unique understanding of Irish agricultural advisors' attitudes to their role in, and capability to deliver, farm succession and inheritance advice.